Exploring the Use of Dimethyl Fumarate as Microglia Modulator for Neurodegenerative Diseases Treatment - Maria Rosito; Claudia Testi; Giacomo Parisi; Barbara Cortese; Paola Baiocco; Silvia Di Angelantonio (MDPI AG, 2020)
The maintenance of redox homeostasis in the brain is critical for the prevention of the development of neurodegenerative diseases. Drugs acting on brain redox balance can be promising for the treatment of neurodegeneration. For more than four decades, dimethyl fumarate (DMF) and other derivatives of fumaric acid ester compounds have been shown to mitigate a number of pathological mechanisms associated with psoriasis and relapsing forms of multiple sclerosis (MS). Recently, DMF has been shown to exert a neuroprotective effect on the central nervous system (CNS), possibly through the modulation of microglia detrimental actions, observed also in multiple brain injuries. In addition to the hypothesis that DMF is linked to the activation of NRF2 and NF-kB transcription factors, the neuroprotective action of DMF may be mediated by the activation of the glutathione (GSH) antioxidant pathway and the regulation of brain iron homeostasis. This review will focus on the role of DMF as an antioxidant modulator in microglia processes and on its mechanisms of action in the modulation of different pathways to attenuate neurodegenerative disease progression.